Answer:
- (h-g)(x) = -3x² + 9x - 19
Explanation:
f(x) = 4x+1
g(x) = 2x²-6x
h(x) = -x² + 3x - 19
a)
(h-g)(x) = h(x) - g(x)
= -x² + 3x - 19 - (2x²-6x)
= -x² + 3x - 19 - 2x² + 6x
combining like terms: -x² - 2x² = -3x², 3x+6x = 9x
= -3x² + 9x - 19
Therefore,
(h-g)(x) = -3x² + 9x - 19
b)
(f-h)(x) = f(x) - h(x)
= 4x+1 - (-x² + 3x - 19)
= 4x+1 + x² - 3x + 19
combining like terms: 4x- 3x = x, 1+19 = 20
= x² + x + 20
Therefore,
(f-h)(x) = x² + x + 20
c)
g(f(5)) = ?
First determine f(5) by substituting x = 5 in the function f(x)
f(x)=4x+1
f(5) = 4(5) + 1
f(5) = 20+1
f(5) = 21
so
g(f(5)) = g(21)
now
substituting x = 21 in the function g(x)
g(x) = 2x²-6x
g(21) = 2(21)² - 6(21)
g(21) = 882 - 126
g(21) = 756
Therefore,
g(f(5)) = 756